Acceptability of Chicken Liver, Egg, and Coconut Milk Enteral Formula (HATASA) as an Alternative for Managing Wasting in Toddlers - Yahya Saputri, Emma; Ayu Saputri, Nanda; Nur Isnaeni, Farida; Puspitasari, Dyah Intan (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: Wasting in toddlers remains a significant problem affecting growth and development, requiring affordable and nutritionally adequate interventions such as enteral formulas based on local food ingredients. Objective: This study aimed to evaluate the acceptability of an enteral formula made from chicken liver, eggs, and coconut milk as an alternative for managing wasting in toddlers. Method: A combination of true experimental and quasi-experimental research with a completely randomized design was conducted from July to August 2025 using three formulations (F1, F2, F3). Chicken liver flour was produced through drying at 90°C for 3 hours, followed by grinding and sieving. Organoleptic testing involved 15 untrained panelists using a 7-point hedonic scale, and data were analyzed using Kruskal-Wallis and Mann-Whitney tests. Result and Discussion: The shrinkage of chicken liver into flour reached 86.7% and 93.05%. Osmolality values ranged from 258-296 mOsm/kg, lower than the commercial product (491 mOsm/kg), while moisture content ranged from 3.76-4.02%, comparable to the commercial product (3.77%). Flow rate ranged from 0.56-1.20 sec/ml. Color values showed l* 31.4-39.9, a* 3-3.45, and b* 7.8-10.4 with no significant differences (p>0.05). Organoleptic results indicated that Formula 1 had higher preference scores (color 5.73, aroma 4.80, overall 4.73) compared to other formulas, although taste, texture, and overall aspects showed significant differences (p<0.05). Higher chicken liver content tended to reduce acceptability, particularly in taste. Conclusions: The best formula was F1 (20 g chicken liver flour and 20 g egg flour), which showed the highest overall acceptability and comparable physical characteristics.